Rapid eradication of vancomycin and methicillin-resistant Staphylococcus aureus by MDP1 antimicrobial peptide coated on photocrosslinkable chitosan hydrogel: in vitro antibacterial and in silico molecular docking studies - Ekhtiari-Sadegh, Sarvenaz; Samani, Saeed; Barneh, Farnoosh; Dashtbin, Shirin; Shokrgozar, Mohammad Ali; Pooshang Bagheri, Kamran (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Antibiotic resistance and weak bioavailability of antibiotics in the skin due to systemic administration leads to failure in eradication of vancomycin- and methicillin-resistant Staphylococcus aureus (VRSA and MRSA)-associated wound infections and subsequent septicemia and even death. Accordingly, this study aimed at designing a photocrosslinkable methacrylated chitosan (MECs) hydrogel coated by melittin-derived peptide 1 (MDP1) that integrated the antibacterial activity with the promising skin regenerative capacity of the hydrogel to eradicate bacteria by burst release strategy. Methods The MECs was coated with MDP1 (MECs-MDP1), characterized, and the hydrogel-peptide interaction was evaluated by molecular docking. Antibacterial activities of MECs-MDP1 were evaluated against VRSA and MRSA bacteria and compared to MECs-vancomycin (MECs-vanco). Antibiofilm activity of MECs-MDP1 was studied by our novel ‘in situ biofilm inhibition zone (IBIZ)’ assay, and SEM. Biocompatibility with human dermal fibroblast cells (HDFs) was also evaluated. Results and Discussion Molecular docking showed hydrogen bonds as the most interactions between MDP1 and MECs at a reasonable affinity. MECs-MDP1 eradicated the bacteria rapidly by burst release strategy whereas MECs-vanco failed to eradicate them at the same time intervals. Antibiofilm activity of MECs-MDP1 were also proved successfully. As a novel report, molecular docking analysis has demonstrated that MDP1 covers the structure of MECs and also binds to lysozyme with a reasonable affinity, which may explain the inhibition of lysozyme. MECs-MDP1 was also biocompatible with human dermal fibroblast skin cells, which indicates its safe future application. The antibacterial properties of a photocrosslinkable methacrylated chitosan-based hydrogel coated with MDP1 antimicrobial peptide were successfully proved against the most challenging antibiotic-resistant bacteria causing nosocomial wound infections; VRSA and MRSA. Molecular docking analysis revealed that MDP1 interacts with MECs mainly through hydrogen bonds with reasonable binding affinity. MECs-MDP1 hydrogels eradicated the planktonic state of bacteria by burst release of MDP1 in just a few hours whereas MECs-vanco failed to eradicate them. inhibition zone assay showed the anti-biofilm activity of the MECs-MDP1 hydrogel too. These findings emphasize that MECs-MDP1 hydrogel would be suggested as a biocompatible wound-dressing candidate with considerable and rapid antibacterial activities to prevent/eradicate VRSA/MRSA bacterial wound infections.